DEA-based Malmquist productivity indexes for understanding courts reform. (June 2018) - Falavigna, Greta; Ippoliti, Roberto; Ramello, Giovanni B.
Abstract: Currently there is no clear empirical evidence as to which the most appropriate reform to improve national judicial systems might be, i.e., whether it is better to implement a policy which focuses on judges and their incentives or, alternatively, a policy aimed at reorganizing the courts' structure. The judicial system, like many other sectors of the public administration, is an industry producing a specific good – justice – and, accordingly, it can be studied by using the customary tools of production theory. The paper applies the two-stage analysis by Simar and Wilson (2007) and the Malmquist index to the judiciary, in order to better understand the impact of a specific policy on the productivity of the Italian tax judiciary. The results highlight strong heterogeneity among courts, depending on their geographical location, with North-West and North-East of Italy as the most efficient macro areas. Moreover, by decomposing the index into change in efficiency and change in technology, this work provides a further glimpse into the judiciary's production organization. Interestingly, the evidence shows that a reduction in the number of active sections has had a negative impact on the overall performance of the courts (i.e., a negative change in efficiency of 0.0103, with a p-value  < 0.01), although the reorganization of the residual sections has possibly determined a more effective use of the remaining resources (i.e., a positive change in technology of 0.00285, with a p-value  < 0.01). Hence, technology does not fully replace the productive role of the judges. The overall results suggest that adjudication is a labor-intensive activity and, although fine-tuning their organization can indeed enhance the productivity of the courts, the role of the judges still remains pivotal. There might indeed be ways to increase the efforts made by judges and a suitable policy should create incentives aimed at boosting their productivity. Highlights: The paper analyses the impact of a policy aimed at improving judicial productivity. Results show a more efficient organization but generalized decrease in productivity. The policy has not considered judges and their limits in terms of productivity.